The "MATHEMA" application as a Mathematics Learning Media for Children with Down Syndrome - Amatullah, Fadilah Halfa; Sunardi, Sunardi; Annisi, Mughi Puspa (Journal of ICSAR, 2023)
This research aims to create application-based learning media to help ease children with Down syndrome in learning mathematics. The research method used is a qualitative method, with research subjects of teachers, parents, and children with Down syndrome grade three SDLB. In accordance with the results of the analysis of objective conditions of the ability, inability, and needs of the subject, as well as theoretical analysis of learning mathematics, a 'Mathema' application was developed, namely an interactive learning media in which there are features to learn about the concept of numbers, number sequences, number symbols, and addition and subtraction operations, which based on conceptual validation is feasible to use and based on empirical validation has proven effective for improving the ability to learn mathematics in the subject so that the findings of the 'Mathema' media are expected a solution for teachers in helping ease learning mathematics in children with Down syndrome.